SENYAWA ANTIMAKAN TRITERPENOID ALDEHID DALAM BIJI SIRSAK (Anonna muricata Linn) - Sri Rahayu Santi (Jurnal Kimia (Journal of Chemistry), 2011)
Isolation and identification of active antifeedant compounds from sirsak seed (Anonna muricata Linn) has been carried out. As much as 13 g of concentrated methanol extract was resulted from 1.9 kg dried sirsak seed that was macerated using methanol. Further, this extract was partitioned with n-hexane to obtained 2 concentrated extracts in n-hexane and methanol. The result of antifeedant test of both extracts showed that n-hexane extract was more active than methanol extract.Separations of n-hexane extract using column chromatography (stationary phase: silica gel 60 and mobile phase: ethylacetate-chloroform 5:2) resulted in three fractions with FA fraction as the most active antifeedant (84,6% at 1600 ppm concentration).The identification using phytochemical test and spectrophotometer analysis showed that the isolate (FA. fraction) was triterpenoid aldehyde compound which absorbed at 227.6 nm, 275.1 nm and it had functional groups such as C-H stretching vinyl (3008.7 cm-1), two bands C-H streching aliphatic (2923.9 and 2854.5 cm-1) showing aldehyde group, and carbonyl group C=O (1743.5-1712,7 cm-1).